Bacia do Ribeirão Cachoeira de Cima, Itapagipe (MG): avaliação ambiental integrada e alternativas de uso - Martins, Alécio Perini (2009)
Ribeirão Cachoreira de Cima s watershed is located in the municipality Itapagipe, west mesoregion portion of Triângulo Mineiro and Alto Paranaíba (Minas Gerais) and presents a system of fundamental importance for the municipality because it s responsible for the water supply to the urban population and for taking part of the county's dairy herd, which has in its production of milk and derivatives one of its main economic activities. The developed research aimed to complete the precipitation monitoring and the environmental and integrated evaluation of the basin, covering not only the environmental preservation issue and, also, the alliance between preservation and socioeconomic development, trying to promote sustainable development of the studied area and ensuring the water maintenance regime of the basin. The necessity of conducting an environmental evaluation is justified by the fact that the system has significant physical and environmental diversity, showing areas of residual relief, very sandy soil and high vulnerability areas with natural and physical-environmental ideas for the development of several farming activities in an area of relatively small portion of about 210 km ². The integration of these elements, combined with different types of land use, most of times inadequate, leads the system to a state of alert for the production of water use and availability of this resource in adequate quantity and quality to support all the activities developed in a medium/long period of time. According to these information, it is also justified the rainfall monitoring made, which can optimize the rainwater use and reduce its negative impacts on the system. From the results of the environmental and integrated evaluation and the rainfall monitoring, we intend to propose actions the aim recovering the environmental quality of the Ribeirão Cachoreira de Cima s basin, providing better management, handling and conservation of the natural resources.